Efficacy of a Spanish modified live virus vaccine against homologous porcine reproductive and respiratory syndrome virus infection - Alvarez, A.=700 1 Fernandez Garcia, A.; Prieto, C.; Martinez Lobo, J.; Simarro, I.; Castro, J.M.
(Es, En)
ilus., 36 ref.
Keywords: VACUNA VIVA; INMUNIZACION; CERDO; VIROSIS; ESPAÑA; VIRUS DEL SINDROME REPRODUCTOR Y RESPIRATORIO PORCINO